A simple efficient anchor-free node localization algorithm for wireless sensor networks. (April 2017) - Du, Tao; Qu, Shouning; Guo, Qingbei; Zhu, Lianjiang
In wireless sensor networks, node localization is the first operation after deployment, and the efficiency of localization can directly influence the performance of the wireless sensor network, so designing an efficient localization algorithm has been an important focus in wireless sensor network research. Currently, anchor-free algorithms are the focus of research in node localization because they have the advantages of flexible structure, low cost, high stability and good extensibility. In this article, related research studies of unique localization-, angle- and distance-obtaining methods are introduced, and existing algorithms are analysed. Based on the analysis of existing research, an anchor-free localization algorithm named ladder diffusion node localization algorithm is proposed, in which sensor nodes are located by directional diffused activation and acknowledgement packets with fixed energy. In ladder diffusion node localization algorithm, the time cost of localization is greatly reduced, the communication tasks in localization are allocated in a more balanced manner, and node locations are obtained mainly by rigorous computation instead of measurement, which can reduce transmission measurement error. Finally, the performance of ladder diffusion node localization algorithm is proved both in theory and by the simulation results of experiments.